ANTI-TERRORISM EFFORTS IN INDONESIA - Juwana, Hikmahanto (UI Scholars Hub, 2014)
Terrorism is defined generally under the Anti-Terrorism Law as the intentional use of ‘violence or the threat of violence to create a widespread atmosphere of terror or fear in public’. Indonesia is a victim of terrorism, but at the same time, a safe haven for terrorists. The Indonesian government has taken various measures to eradicate terrorism, yet the Anti-Terrorism Law has not been effective in eradicating terrorist acts in Indonesia. Implementation and enforcement of Anti-Terrorism Law has not been an easy task. Terrorism for Indonesia is a complex and multifaceted issue. This article argues that the successful experience of some other countries in eradicating terrorism may not be applicable to Indonesia. Indonesia has peculiar problems which require anti-terrorism efforts to be sufficiently sensitive to the local context.